2001
DOI: 10.1042/cs20000111
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency heart rate variability: reproducibility in cardiac transplant recipients and normal subjects

Abstract: Heart rate variability is a measure of autonomic nervous influence on the heart. It has been suggested that it could be used to detect autonomic reinnervation to the transplanted heart, but the reproducibility of the measurement is unknown. In the present study, 21 cardiac transplant recipients and 21 normal subjects were recruited. Three measurements of heart rate variability were performed during the day: in the morning, in the early afternoon and in the late afternoon. These tests were then repeated 1 week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…[7][8][9]33 In addition, MIBG uptake showed only partial sympathetic reinnervation post-HTx in some but not all recipients, never reaching global cardiac reinnervation. 35,47 Furthermore, heart rate variability (HRV) was noted to be different in transplant recipients from time to time during the day, 52 which could be evidence for the heterogeneity of reinnervation.…”
Section: Cardiac Reinnervationmentioning
confidence: 99%
“…[7][8][9]33 In addition, MIBG uptake showed only partial sympathetic reinnervation post-HTx in some but not all recipients, never reaching global cardiac reinnervation. 35,47 Furthermore, heart rate variability (HRV) was noted to be different in transplant recipients from time to time during the day, 52 which could be evidence for the heterogeneity of reinnervation.…”
Section: Cardiac Reinnervationmentioning
confidence: 99%
“…Our results are comparable with previous reliability studies in healthy subjects [11] and post-myocardial infarction patients [14], which reported similar 95% limits of random variation for time domain parameters, albeit narrower limits for frequency domain parameters. However, similarly poor absolute reliability of spectral measures has been identified in patients with chronic heart failure [15] and cardiac transplant recipients [16].…”
Section: Absolute Reliability Of Hrvmentioning
confidence: 99%
“…These are, overall, slightly higher than those generated by all three systems used in the present study. Lord et al (2001) studied the reliability of the LF oscillations in the frequency domain to assess this variable's usefulness in intervention studies. The LF component was found to show poor reliability in both normal subjects (CV ¼ 45%) and in heart transplant recipients (CV ¼ 76%).…”
Section: Mean Valuementioning
confidence: 99%
“…There is a significant body of data regarding the reliability of 24-h recordings (Zuanetti et al, 1991;Durant et al, 1992;Ziegler et al, 1999;Yi et al, 2000), yet investigations into the reliability of short-term measures of HRV are less numerous. Of those published, many concern the use of HRV during tests or manoeuvres (Bootsma et al, 1996;Jauregui-Renaud et al, 2001;Lord et al, 2001). There is a scarcity of studies concerning HRV measurements made under stable, resting conditions and published results vary in terms of estimates of reliability (Ponikowski et al, 1996;Sinnreich et al, 1998;Marks & Lightfoot, 1999).…”
Section: Introductionmentioning
confidence: 99%